Botany up to date - Damasceno, Simone Alves (2021)
The present material is a reference source for Science and Biology teachers, whose purpose is to address Botany in the classroom in a precise and dynamic way. It is expected that this area of ​​Biology will no longer be seen as difficult or complex to be treated. First, we selected contents of Plant Anatomy and Morphology, for an overview of this area of ​​knowledge. Next, Plant Physiology is addressed from the photosynthesis process, along with elements such as pigments and organelles. In addition, the stages of photosynthesis and some plants with mechanisms C3, C4 and, finally, CAM are indicated. We expect that the use of this didactic tool will be useful in Botany classes, serving as a stimulus to show, when necessary, the real meaning and importance that plants and this area of ​​knowledge have for life, in its various forms.